Negative bias temperature instability and permittivity dependent delay mitigation in High-K metal oxide compatible cmos dielectric / Nissar Mohammad Karim - Nissar, Mohammad Karim (2015)
Negative Bias Temperature Instability (NBTI) and oxide delay are considered as threats to Complementary Metal Oxide Semiconductor (CMOS) transistors. Improving these issues result in improved performance in terms of reliability. In this thesis, to ensure reliability in transistors, the results on the basis of NBTI and oxide delay have been reported by incorporating SiO2 dielectric with different aged samples of high-K metal oxides. ZnO, TiO2 and CuO are chosen for the incorporation. NBTI occurs due to negative biasing and high temperature. And, oxide delay occurs due to high resistance and high capacitance inside dielectric. In this thesis the objectives are: to mitigate oxide delay; to mitigate threshold voltage change due to NBTI effect in CMOS device; and having mitigated NBTI in device level, to analyze the compatibility of radio frequency in circuit level considering NBTI effect. Precursor ageing of the incorporated materials is carried out for 2, 3 and 4 days. Each aged sample is treated under UV light for 1, 2 and 3 hours. From the experiments 9 samples are prepared for each type of metal oxide incorporation. From all these samples, the minimum and maximum dielectric constant after ageing and UV treatment were extracted. The minimum valued sample with the lowest dielectric constant is chosen for obtaining the lowest time delay. The maximum value is employed to check threshold voltage increase due to NBTI since a high value of dielectric constant will minimize threshold voltage and will increase the drive current. A PerkinElmer Lambda 35 Filmetrics system, Scanning Electron Microscopy and Energy Dispersive X-ray Microanalysis are employed to characterize the films. For ZnO, results show that the smallest obtainable dynamic dielectric constant is 1.1925 which is found by examining the one hour UV exposed precursor sample after four days. For TiO2, Results show that the smallest obtainable dynamic dielectric constant is 1.0294 which is found by examining the one hour UV exposed precursor sample after two days. And, for CuO, Results show that the smallest obtainable dynamic dielectric constant is 4e-08 which is found by examining the one hour UV exposed precursor sample after three days. While exploiting the maximum refractive index in NBTI predictive model, significant improvements were found in TiO2 and CuO. The extracted dielectric constants parameters from refractive index were employed and simulated inside the predictive model. Under DC stress, exploiting cured sample (4 days aged and 3 hours UV exposed) of TiO2 results in a 70% increase in drive current and exploiting cured sample (4 days aged and 2 hours UV exposed) of CuO results in 98% increase in drive current. Under AC or dynamic bias stress, exploiting cured sample (4 days aged and 3 hours UV exposed) of TiO2 results in a 65% increase in drive current and exploiting cured sample (4 days aged and 2 hours UV exposed) of CuO results in 98% increase in drive current. Having been able to perform the device level NBTI induced performance enhancement for cured TiO2 and cured CuO, a forecasting algorithm was developed for circuit level to predict frequency compatibility under NBTI effect. The analysis is carried out under different radio frequency spectrums. An oscillator was selected as a target circuit to elaborate the NBTI circuit level algorithm which resulted in 2~4 GHz frequency spectrum as the most compatible frequency range for the circuit under NBTI effect since this range obtains highest gain for pure SiO2, TiO2 incorporated SiO2 and CuO incorporated SiO2. TiO2 incorporation shows 45% increment in gain over pure SiO2. And CuO incorporation shows 46% increment in gain over pure SiO2. This data was found by employing experimentally obtained refractive index data into the developed algorithm.